Supervisory beliefs and practices of instructional leaders: a case study / Adzlina Ibrahim - Ibrahim, Adzlina (2013)
The purpose of the study was to examine supervisory beliefs and practices of Instructional Leaders in a secondary school in Kuala Langat. The descriptive study case study comprised 72 Instructional Leaders which involved 29 middle managers and 43 teachers. The study employed a mixed methods research design where data were collected using a questionnaire and semi structured interviews. Three middle managers and three teachers were randomly selected for the semi structured interviews. The quantitative data were analysed using Statistical Package for Social Sciences (SPSS) version 17. Frequencies, percentage, mean, standard deviation and t-test were conducted from the data. The validity and reliability of the instruments was established through experts' opinions and a pilot study. The findings revealed between directive approach, collaborative approach and nondirective approach, middle managers take 53.6% of the time use directive approach to supervision while teachers stated middle managers take 87.1% of the time use collaborative approach to supervision. Findings also indicated middle managers and teachers have high level of implementing supervision practices. However teachers did have moderate perception towards implementing the evaluation stage. On the other hand, the finding indicated that there was no significant difference of supervisory practices between teachers' perception and middle managers' perception t (72) = 0.46, p-value = 0.65. Through semi-structured interviews, the result revealed that middle managers and teachers faced problems like time constraint, the purpose of supervision and lack of facilities in school. In addition middle managers faced problems with senior teachers and teachers as they questioned the supervisor's credibility. Overall, the findings of this study imply that instructional leaders need to be aware of effective supervision practices as it can enhance the teaching and learning process. It may also serve as a platform to motivate instructional leaders to change the role of school head, middle managers and teachers in the way to enhance supervision practices in school. Based on the findings, future research may examine the real impact of supervisory practices on student learning outcomes. Further investigations on demographic characteristics, difference schools and intensity of the supervisory practices being carried out may be conducted in the future.